A doomful of sugar - Bruns, Catherine (Bruns, Catherine. Maple syrup mysteries, 2022)
"First in a new cozy mystery series! There's nothing sweet about murder... Leila Khoury has always believed that everyone loved her father as much as they loved his artisanal maple syrup. But when he's killed, and she returns to Sugar Ridge, Vermont to take over his business, she starts to realize how much of his life she's left untapped. With her brother under suspicion, her mother just barely holding it together, and police not producing any leads, Leila will have to investigate herself if she wants answers about her father's sticky end. But the more she learns, the more she worries that there won't be a sappy ending to the story. A cozy mystery perfect for fans of Joanne Fluke, this edition includes 5 delicious maple recipes for mystery readers with a sweet tooth!"--